Molecular detection and phylogenetic analysis of Anaplasma phagocytophilum bacteria in cows and it is infested ticks in Mosul city, Iraq - Abeer Alnakeeb; Qaes Al-Obaidi (Basrah Journal of Veterinary Research)
The present study was conducted to molecular detection of Anaplasma phagocytophilum in infected cows and it is infested ticks in Mosul, Iraq using nested polymerase chain reaction technique (N-PCR) and to investigate the phylogenetic analysis of A. phagocytophilum diagnosed in this study. A total of 50 blood samples (3 ml) were collected from cows in various areas of Mosul city. Additionally, 169 hard ticks were collected from different parts of infected cows. Results revealed that the infection rate of A. phagocytophilum in cows at Mosul city was 72% and in engorged female ticks was 81.2% using N-PCR technique. The infestation rate hard ticks on cows were 46% and four species of hard ticks were microscopically identified and classified includes Hyalomma anatolicum anatolicum (39.64%), Rhipicephalus turanicus (21.89%), Rh. sanguineus (23.07%) and Boophillus annulatus (15.38%) with significantly predominant Hyalomma anatolicum anatolicum. The individual sequencing analysis for five sequences of 16S rRNA gene includes: one extracted from cow blood and four extracted from engorgement female ticks. The sequences of A. phagocytophilum were recorded in the NCBI Genbank under the accession numbers (OR002120.1, OR002121.1, OR002122.1, OR002123.1 and OR002124.1). These sequences were highly identity (100%) to those sequences recorded in the NCBI Genbank such as (MT221233.1, MT221234.1) in Norway, (MK239930.1, MK239931.1) in Southern Korea, (MN170722.1, MN170722.1) in Spain, (MK814411.1, MK814412.1) in South Africa, (LC435049.1, LC435050.1) in Japan and (MH122889.1, OQ727069.1) in Poland, and Malawi respectively. This finding might be advantageous for the future studies and strategically control of this bacterium in the study area.